Gendering a Warbot: GENDER, SEX AND THE IMPLICATIONS FOR THE FUTURE OF WAR. Issue 1 (2nd January 2016) - Roff, Heather M.
Abstract: Recently, the United States Defense Advanced Project Agency (DARPA) hosted its "Robotics Challenge." The explicit goal of this challenge is to develop robots capable of "executing complex tasks in dangerous, degraded, human engineered environments." However, the competitors' choice to build humanoid robots tells a different narrative. In particular, through the physical design choices, the giving of names and the tasking of roles, the competing teams perpetuated a gendered narrative. This narrative in turn reifies gendered norms of warfighting, and ultimately leads to an accretion of gendered practices in militaries, politics and society, despite contemporary attempts at minimizing these practices through policies of inclusion. I argue that though much work on gender and technology exists, the autonomous humanoid robot – the one currently sought by DARPA – is something entirely new, and must be addressed on its own terms. In particular, this machine exceeds even Haraway's conception of the post-human cyborg, and rather than emancipating human beings from gender hierarchy, further reifies its practices. Masculine humanoid robots will be deemed ideal warfighters, while feminine humanoid robots will be tasked with research or humanitarian efforts, thereby reinstituting gendered roles.